Application of ponding systems in the treatment of palm oil mill and rubber mill eflluents - Wong, Kien Kuok (Universiti Pertanian Malaysia, 1980)
Ponding is proposed as a viable low-cost treatment method for .palm oil and rubber mill effluents. Theoretical considerations were reviewed and discussed in relation to the design of ponds. Both empirical and rational design models were presented. Adoption of such models were deemed closest to a way of designing ponds. Applications of ponding systems for palm oil mill effluent, rubber effluent and domestic sewage in Malaysia were discussed. Some first order kinetic coefficients were calculated for rubber mill effluents based on data for existing ponding systems. These constants ranged from 0.065 to 0.27 day-I. Kinetic coefficients for palm oil mill effluent for both completely mixed and plug flow systems were also presented. The coefficient for a pond exhibiting plug flow was found to be 0.068 day-t. Insufficient data prevented the derivation of kinetic constants for domestic sewage oxidation ponds. Costs data were derived from existing palm oil mill effluent anaerobic treatment systems for comparison between ponding and other systems.